2019
DOI: 10.1002/mus.26781
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional area reference values for sonography of nerves in the upper extremities

Abstract: Introduction Detailed morphological features of the peripheral nerves could improve the diagnostic sensitivity in some polyneuropathies. In this study we aimed to establish multiple‐site, cross‐sectional area (CSA) reference values for peripheral nerves of upper extremities in a healthy Chinese population. Methods One hundred eleven healthy subjects, 15 to 70 years of age, were prospectively recruited. CSA at predetermined sites of the median, ulnar, radial nerves, and brachial plexus was measured bilaterally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
47
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 30 publications
24
47
2
Order By: Relevance
“…Our CSA reference values are closer to those of Korea and Japan, and smaller than those of the United States. Similar differences among races were also seen in other peripheral nerves, according to our previous work 13 …”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our CSA reference values are closer to those of Korea and Japan, and smaller than those of the United States. Similar differences among races were also seen in other peripheral nerves, according to our previous work 13 …”
Section: Discussionsupporting
confidence: 88%
“…Similar differences among races were also seen in other peripheral nerves, according to our previous work. 13 According to the previous studies, when compared with HC, the CSA of vagus nerve was larger in CMT1B and CIDP patients. 3,4 We confirmed that the mean CSA of the vagus nerve was larger in CMT1A and CIDP patients compared with HC.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations